Food and Famine in Colonial Kenya - Duminy, James (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book offers a genealogical critique of how food scarcity was governed in colonial Kenya. With an approach informed by the 'analysis of government', the study accounts for the emergence and persistence of dominant approaches to promoting food security in Kenya and elsewhere in Africa - policies and practices that prioritize increased agricultural production as the principal means of achieving food security. Drawing on a range of archival sources, the book investigates how those tasked with governing colonial Kenya confronted food as a particular kind of problem. It emphasizes the ways in which that problem shifted in conjunction with the emergence and consolidation of the colonial state and economic relations in the territory. The book applies a novel conceptual approach to the historical study of African food systems and famine, and provides the first longitudinal and in-depth analysis of the dynamics of food scarcity and its government in Kenya. James Duminy is Lecturer in Human Geography at the University of Bristol, UK.
1. Introduction.-2. Famine and Colonial Conquest.-3. Scarcity, State Control and the First World War -- 4. Scarcity and Settler Consolidation -- 5. Depression and Scarcity -- 6. Scarcity, State Control and War: Redux -- 7. Setting the Agenda -- 8. Conclusion.
Keywords: Africa-History.; Imperialism; Africa-Politics and government; African History; Imperialism and Colonialism; African Politics